Pengaruh Citra Merek Dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Yamaha Merek Mio M3 Pada PT Hasjat Abadi Outlet Maumere - Todang, Kornelia Selvi; Rangga, Yoseph Darius Purnama; Gula, Valeria Eldyn (Universitas Nusa Nipa Maumere, 2026)
This study aims to determine the influence of brand image and promotion on the purchasing decisions of Yamaha Mio M3 motorcycles at PT Hasjrat Abadi Outlet Maumere. This research employed a quantitative descriptive method with an associative approach. The population consisted of all Yamaha Mio M3 consumers at PT Hasjrat Abadi Outlet Maumere over the last three years, totaling 62 respondents. A saturated sampling technique was applied, in which all members of the population were used as the research sample. Data were collected through a literature review and questionnaires distributed using a Likert scale. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of IBM SPSS Statistics software. The results indicate that brand image and promotion partially have a significant effect on purchasing decisions. Simultaneously, brand image and promotion also have a significant effect on the purchasing decisions of Yamaha Mio M3 motorcycles at PT Hasjrat Abadi Outlet Maumere. The coefficient of determination (R²) shows that brand image and promotion contribute 67.6% to purchasing decisions, while the remaining 32.4% is influenced by other factors not examined in this study. Therefore, brand image and promotion play an important role in improving consumers’ purchasing decisions for Yamaha Mio M3 motorcycles.